Effects of Erythromycin on Beta Cells of Pancreas - Abidi, Taquayya Sultana; Khan, M. Shahid Anwar (Journal of Postgraduate Medical Institute, 2011)
The study was formulated on 56 albino rats divided into one control and two experimental groups, for the observation of the effects of erythromycin ( 2 Gm / 70 Kg / day for 28 days and 3 Gm/ 70Kg / day for 28 days) on the beta cells of islets of langerhans of Pancreas. Group I – A and II – A animals were studied for immediate effects of treatment, while group I – B and II – B animals were studied for the delayed effects after the cessation of the drug. The erythromycin's activity on beta cells appears to be a stimulating one for the production and release of insulin, but does not prove to be harmful as it did not cause any appreciable damage which could have been demonstrated histologically. It however causes a drop in the blood sugar level which reverted after the cessation of the treatment, indicating that permanent damage did not occur. Observing its stimulating effect on the beta cells, in our opinion, due precautionary measures should be taken for its use along with the drugs which lower the blood sugar level by the beta cell stimulation, as Erythromycin may enhance their effects.